MANAJEMEN KONFLIK DAN RESILIENSI SISWA SEBAGAI MITIGASI DAMPAK BULLYING TERHADAP MENTAL HEALTH - Anggraini, Puput; Mahmudi, Rois (As-Sulthan Journal of Education, 2024)
This research aims to analyze conflict management and student resilience in an effort to mitigate the impact of bullying on mental health. Using a qualitative approach with a case study type, this research involved students, teachers and counselors from secondary schools that had significant cases of bullying. Data was collected through in-depth interviews, observation and documentation studies, then analyzed using thematic methods. The research results show that mediation-based conflict management and strengthening student resilience through empathy, communication and social support training are effective in reducing the negative impact of bullying. Students who have a high level of resilience tend to be better able to deal with psychological pressure due to bullying, while a conflict management approach increases collective awareness in creating a more supportive environment. This research contributes to the development of practical strategies for schools in dealing with bullying, as well as providing new insights into the links between conflict management, resilience and student mental health.